HYPERPARATHYROIDISM - Ahmed, Nazir; Sultan, Syed; Saeed, A. Karim (Journal of Ayub Medical College Abbottabad, 1988)
Excessive secretion of Parathyroid Hormone may be primary due to adenoma or hyperplasia of the parathyroid glands, secondary due to persistent hypocalcaemia or tertiary when secondary hyperplasia leads to autonomous over activity of the glands. Whatever the cause increase PTH production leads to hypercalcaemia. This may be symptomless or may present with bizarre symptoms such as psychosis, renal stones, anorexia, abdominal pain, polyurea, osteoporosis, pathological fractures and deformities.